Associations Between Serum Soluble α-Klotho and the Prevalence of Specific Cardiovascular Disease - Xu, Jun-Peng; Zeng, Rui-Xiang; He, Mu-Hua; Lin, Shan-Shan; Guo, Li-Heng; Zhang, Min-Zhou (Frontiers in Cardiovascular Medicine, 2022)
Objective: Accumulating experimental evidence has identified the beneficial effects of the antiaging protein, serum soluble α-Klotho, on longevity and the cardiovascular system. Although a previous study has revealed the predictive value of α-Klotho on total cardiovascular disease (CVD), the associations between α-Klotho and specific CVDs, including congestive heart failure (CHF), coronary heart disease (CHD), myocardial infarction (MI) and stroke, remain to be fully elucidated in humans. Methods: For 8,615 adults in the 2007 to 2016 National Health and Nutrition Examination Survey, stratified multivariable logistic regression models, restricted cubic spline curves and subgroup analyses were used to evaluate the associations between α-Klotho and the four specific CVDs. Results: In the quartile analyses, compared to those in the highest quartile, participants in the lowest level of α-Klotho were significantly associated with CHF (OR = 1.46, 95% CI: 1.09-1.97) and MI (1.33, 1.02-1.74), which was not the case for CHD (1.12, 0.91-1.38) or stroke (0.96, 0.73-1.25). Each unit increment in ln-transformed α-Klotho concentrations was only positively associated with 38% and 24% reduction in the prevalence of CHF and MI, respectively. Restricted cubic spline curves indicated that α-Klotho was correlated with CHF and MI in linear-inverse relationships. Conclusions The present findings suggested that serum soluble α-Klotho is significantly associated with the prevalence of CHF and MI. To better determine whether α-Klotho is a specific biomarker of CVD, particularly for CHD and stroke, further research in humans will be needed.